Network Security Hacks - Lockhart, Andrew (O'Reilly, 2011)
This information-packed book provides more than 100 quick, practical, and clever things to do to help make your Linux, UNIX, or Windows networks more secure. Loaded with concise but powerful examples of applied encryption, intrusion detection, logging, trending, and incident response, Network Security Hacks demonstrates effective methods for defending your servers and networks from a variety of devious and subtle attacks.